Evaluation of solidified and stabilized shipyard abrasive blasting waste as construction material / Salmaliza Salleh - Salmaliza , Salleh (2018)
Tons of abrasive blasting wastes (ABW) are produced each year from the removal of old paint from the ships. The abrasives contain heavy metals which are considered hazardous by the Toxicity Characteristic (TC) criteria. This research describes an investigation of cement-based solidification and stabilization (S/S) of the spent abrasives from ship repair, which is mainly spent copper slag. ABW which are mixed with Ordinary Portland cement (OPC) ranging from ratio of 0 to 1.5 by weight of cement were tested for crushed block leachability and compressive strength. The water-to-cement ratio of the mixes was set at 0.35 to 0.5. The results indicated that the leaching of selected heavy metal ions from the cement matrix was low and did not exceed the United States Environmental Protection Agency (US EPA) and Malaysian Department of Environment (DOE) Regulation Guidelines. However, addition of abrasive blasting waste to cement increased the initial setting times, which retards the process of hardening of the cement matrix. The strength of the S/S abrasives was generally lower than the control cement paste. Optimum strength achieved when the ratio of C/ABW is 1.5 with water-to-cement ratio of 0.35. In the next stage of study, sand was added in the cement-ABW matrix to develop bricks for construction purpose. The strength of the C/ABW bricks was generally higher than the control and conventional sand-cement bricks. The optimum strength achieved when 20% of sand weight was replaced by the ABW with water-to-cement ratio of 0.35. The C/ABW brick may be classified as Engineering Brick Type B due to its high strength and low water absorption property. In the later stage, coarse aggregates were added in the C/ABW bricks design matrix to test the possibility of producing concrete with solidified and stabilized Abrasive Blasting Waste as fine aggregates. The results showed that concrete with ABW has reached compressive strength of 79 MPa at 28th day which is classified as high strength concrete.